Enhancing High School Critical Thinking in Geography through Genially-Assisted Game-Based Learning - Acmad Zainur Risla; Fatiya Rosyida; Agung Setiawan (CV Bumi Spasial, 2026)
This research addresses a critical gap in digital geography pedagogy by evaluating the implementation of a Genially-integrated Game-Based Learning (GBL) framework. A primary novelty of this study lies in the technical differentiation of Genially from standard gamified interfaces, such as Kahoot or Wordwall while the latter often emphasize linear rote retrieval, Genially facilitates the synthesis of multi-layered interactive mapping and complex spatial simulations essential for advanced geographic interpretation. The investigation specifically operationalizes critical thinking within the thematic context of Indonesia’s Strategic Position, a topic strategically selected for its inherent spatial complexity and capacity to trigger higher-order cognitive processes. Utilizing a quantitative pseudo-experimental design with a pretest-posttest control group , the study sampled two cohorts (N=71) at SMAN 2 Sumenep: class XI–8 (experimental) and XI–7 (control). Data were collected via essay instruments aligned with C4 (Analysis), C5 (Evaluation), and C6 (Creation) cognitive levels. Analytical procedures involved N-Gain scores and Independent Sample T-tests to quantify shifts in student proficiencies. Empirical findings demonstrate the superior efficacy of Genially-assisted GBL. The experimental group achieved a posttest mean of 81.87, significantly outperforming the control group’s 60.37. Standardized metrics via N-Gain analysis confirmed a moderate growth coefficient of 0.53 for the experimental cohort compared to a negligible 0.06 for the control. Statistical significance (p=0.000) suggests that the Genially-integrated framework serves as a robust catalyst for enhancing analytical reasoning. These results indicate the potential of GBL-driven interventions to facilitate a sophisticated understanding of spatial dynamics, providing a viable evidence-based pathway for modernizing geographic instruction.